Analisis Pengaruh Geometri Peledakan Terhadap Fragmentasi Hasil Peledakan Dan Digging time Alat Gali Muat Backhoe Caterpillar 6030 Pada Area Pit Limit PT. Semen Padang, Indarung, Provinsi Sumatera Barat - Muhammad Tareq Adha; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2021)
PT. Semen Padang is a mining company that uses the open pit mining method, namely Quarry Side Hill mining, which is a mining method carried out to excavate deposits of industrial minerals or non-metallic minerals. The rock to be transported to the crusher must be blasted first. The results of field observations of the actual blasting geometry applied by the company obtained fragmentation of boulder-sized blasting results with a percentage of ±31%. The large percentage of boulder causes the diggability of the digging tool to be not optimal, where the digging time of the digging tool is not according to the company's target of below 12 seconds. This study aims to design the optimum blasting geometry to reduce the percentage of boulder so that loading activities become effective and the diggability of the digging tool increases. The research method is carried out by providing recommendations for blasting geometry based on the methods of C.J Konya and R.L. Ash. The proposed geometry applied in the field is: burden: 3 m, spacing of 3.5 m, stemming: 3 m, subdrilling: 1 m, ladder height: 8 m, blast hole depth: 9 m, powder column: 6 m, and powder factor : 0.26 kg/ton, where the boulder size fragmentation resulting from the analysis is 11.92%.